PENGARUH STRUKTUR KEPEMILIKAN, TINGKAT PROFITABILITAS, TINGKAT LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP RISK MANAGEMENT DISCLOSURE (Studi Survei pada Perusahaan Perbankan yang Listing di Bursa Efek Indonesia Tahun 2012-2013) - Vera Dwi Intan Findiyani, 10.05.52.0033; Suwarti, Titiek (Students Journal of Accounting and Banking, 2014)
This study purpose to investigate the influence of ownership structure, level of probability Â and the level of leverage on the disclosure of risk management of the banking industry in Indonesian Stock Exchange listing. Independent variable in this study is the ownership of domestic institutions, public ownership, level of probability and the level of leverage. The dependent variable in this study is the disclosure of risk management. The sample used in this study is a secondary data derived from the Indonesian Stock Exchange (BEI), the annual report of the banking industry in Indonesian Stock Exchange listing of the years 2012 and 2013. Samples were taken by using purposive sampling method. The samples used were 31 Bank. The method of analysis in this study using multiple regression. The results of this study indicate that the level ownership of institutions, public ownership, level of profitability, leve of leverage, and firm size does not effect the disclosure of risk management.Keywords: Disclosure of risk management, ownership structure, profitability, levegare, Firm Size, stakeholder theory and agency theory